PENEMUAN HUKUM DALAM PUTUSAN MAHKAMAH AGUNG DAN RELEVANSINYA BAGI PENGEMBANGAN HUKUM ISLAM INDONESIA - Budiman, Achmad Arief (Al-Ahkam, 2014)
This qualitative research aimed to criticize the form of legal invention by the Supreme Court (MA) and its relevance to the development of Islamic law on Indonesia. This study also aims to find a model of the development of Islamic law through the dicovery made by the judge when adjudicating the case. The samples of this study were selected verdicts of MA based on the presence or absence of legal invention parameters in it. The result of this study is that the two verdits of MA, precisely describe the form of the legal invention by showing courage and creativity at the same time in deciding the case. The legal invention of MA has significant contribution to the development of Islamic law in Indonesia. Because of the standing points of MA as the top judiciary, it’s verdits would be as jurisprudence for the other judges, especially at the lower level court.